Transtorno de estresse pós-traumático em gestantes com diagnóstico de anomalias congênitas - Aguiar, Michelle Alves Viana [UNIFESP] (2016)
Objective: To evaluate the symptoms of post-traumatic stress disorder (PTSD) in pregnant women with congenital anomaly. Methods: Quantitative study with cross-correlational design. The sample consisted of 111 pregnant women diagnosed with viable and unviable congenital anomaly met in Fetal Medicine Clinic of the Universidade Federal de São Paulo (UNIFESP), from november 2013 to november 2014. The instruments used for data collection were a semi-structured questionnaire and a Likert scale, Impact of Events Scale - Revised (IES-R). For statistical analysis the following tests were used: Qui-square test for categorical variables; Student’s t or Mann-Whitney test for comparisons of continuous variables; the Cronbach Alpha coefficients and Pearson correlation in the areas that make up the scale IES-R; simple linear regression models we used to assess jointly the effect of time of receiving the diagnosis of viable and unviable congenital anomalies, along with the total score and domains of IES-R scale. Results: Viable congenital anomalies corresponded to 66.6% of cases and unviable to 33.3%. Among all cases of congenital anomalies, 27% were related to the nervous system, 24.3% to circulatory and 19.8% to urinary. Unviable congenital anomalies were anencephaly (35.1%) and related to the urinary (27%) and respiratory (24.3%). systems. The most frequent viable congenital anomalies were in nervous (31.1%) and circulatory systems (27%). The diagnosis of congenital anomalies has been established in the second trimester (77.5%). In order to compare the symptoms of PTSD in pregnant women with viable and unviable congenital anomaly, the statistical analysis found that the average of all areas of IES-R (avoidance, intrusion and hyperarousal), as well as the sum of matters concerning IES-R were high in all pregnant women diagnosed with congenital anomaly, however it was higher in pregnant women diagnosed with congenital anomaly unfeasible. Using a cut of 5.6 units in the total score of the IES-R, we found that 46.8% of all pregnant women diagnosed with congenital anomaly showed symptoms of PTSD, but the symptoms were more frequent among pregnant women diagnosed with unviable congenital anomaly (64.9%) than among those with viable fetuses (37.8%). Evaluating the correlation between the domains of the IES-R scale, we noted that the intrusion issues and hyperstimulation were more correlated than the avoidance domain. Among pregnant women diagnosed with both viable and unviable congenital anomaly, we observed a decreasing relationship with the symptoms of PTSD in relation to the time the news of the diagnosis of congenital anomalies was informed. Conclusion: The symptomatology of PTSD was present in pregnant women with both viable and unviable congenital anomaly. PTSD can cause immediate and long-term impact on pregnant women with such diagnoses.